Chemoimmunotherapy for relapsed/refractory and progressive 17p13‐deleted chronic lymphocytic leukemia (CLL) combining pentostatin, alemtuzumab, and low‐dose rituximab is effective and tolerable and limits loss of CD20 expression by circulating CLL cells. Issue 7 (26th April 2014) - Zent, Clive S.; Taylor, Ronald P.; Lindorfer, Margaret A.; Beum, Paul V.; LaPlant, Betsy; Wu, Wenting; Call, Timothy G.; Bowen, Deborah A.; Conte, Michael J.; Frederick, Lori A.; Link, Brian K.; Blackwell, Sue E.; et al.
<x xml:space="preserve">Abstract</x> Chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL) patients with purine analog refractory disease or TP53 dysfunction still have limited treatment options and poor survival. Alemtuzumab‐containing chemoimmunotherapy regimens can be effective but frequently cause serious infections. We report a Phase II trial testing the efficacy and tolerability of a short‐duration regimen combining pentostatin, alemtuzumab, and low‐dose high‐frequency rituximab designed to decrease the risk of treatment‐associated infections and to limit the loss of CD20 expression by CLL cells. The study enrolled 39 patients with progressive CLL that was either relapsed/refractory (n = 36) or previously untreated with 17p13 deletion (17p13−) (n = 3). Thirteen (33%) patients had both 17p13− and TP53 mutations predicted to be dysfunctional, and eight patients had purine analog refractory CLL without TP53 dysfunction. Twenty‐six (67%) patients completed therapy, with only five (13%) patients having treatment‐limiting toxicity and no treatment‐related deaths. Twenty‐two (56%) patients responded to treatment, with 11 (28%) complete responses (four with incomplete bone marrow recovery). Median progression‐free survival was 7.2 months, time to next treatment was 9.1 months, and overall survival was 34.1 months. The majority of deaths (82%) were caused by progressive disease, including transformed diffuse large B‐cell lymphoma (n = 6). Correlative studies showed that low‐dose rituximab activates complement and natural killer cells without a profound and sustained decrease in expression of CD20 by circulating CLL cells. We conclude that pentostatin, alemtuzumab, and low‐dose high‐frequency rituximab is a tolerable and effective therapy for CLL and that low‐dose rituximab therapy can activate innate immune cytotoxic mechanisms without substantially decreasing CD20 expression. Am. J. Hematol. 89:757–765, 2014. © 2014 Wiley Periodicals, Inc.